2017
DOI: 10.1021/acs.langmuir.6b03534
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ellipsoidal Particles at Liquid–Liquid Interfaces

Abstract: The adsorption of particles at liquid-liquid interfaces is of great scientific and technological importance. In particular for non-spherical particles, the capillary forces which drive adsorption vary with position and orientation and complex adsorption pathways have been predicted by simulations. Based on the latter it has been suggested that the time scales of adsorption are determined by a balance between capillary and viscous forces. However, several recent experimental results point out the role of contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…For example, single microparticles adsorbed at liquid-liquid interfaces have exhibited crossovers from initially fast dynamics, driven by capillary forces, to a much slower "kinetic" relaxation that can be nearly logarithmic in time, as first discovered by Kaz et al 5 and subsequently studied by other groups. [6][7][8][9][10] Similar near-equilibrium behavior has been also observed in the imbibition/drainage of water/oil in microscale capillaries with nanoscale surface roughness. 11 The observed near-equilibrium phenomena, resembling physical ageing in dense colloidal systems that exhibit jamming transitions, [12][13][14][15] have been attributed to random thermally activated transitions between multiple metastable states induced by numerous nanoscale "defects" on the solid surface.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…For example, single microparticles adsorbed at liquid-liquid interfaces have exhibited crossovers from initially fast dynamics, driven by capillary forces, to a much slower "kinetic" relaxation that can be nearly logarithmic in time, as first discovered by Kaz et al 5 and subsequently studied by other groups. [6][7][8][9][10] Similar near-equilibrium behavior has been also observed in the imbibition/drainage of water/oil in microscale capillaries with nanoscale surface roughness. 11 The observed near-equilibrium phenomena, resembling physical ageing in dense colloidal systems that exhibit jamming transitions, [12][13][14][15] have been attributed to random thermally activated transitions between multiple metastable states induced by numerous nanoscale "defects" on the solid surface.…”
supporting
confidence: 65%
“…A slow kinetic regime is described by the implicit expression in equation (6) or the explicit logarithmic expression in equation (8), which are derived from the rate equation (equation (4)) for thermally activated transitions between metastable states. Such metastable states correspond to local minima in the free energy profile F(R) given by equation (2), which can only exist when the droplet is sufficiently close to equilibrium and K|R 2 − R 2 E | ≤ ∆F/A d .…”
Section: From Power-law Spreading To Physical Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent experiments have shown that contact line pinning plays a dominant role in the adsorption of anisotropic particles at liquid interfaces. 31,32 However, theories neglecting pinning and contact line hysteresis have proven to serve as useful guidelines for both capillary interactions and self-assembly of anisotropic particles at liquid interfaces. 5,12,17,18 In addition, we believe that contact line pinning is more important in adsorption because the forces driving the motion are small (and become smaller and smaller as we approach the final equilibrium configuration of the particle), whereas pinning is comparatively less important in our system because we are applying a large external torque on each particle.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the diffuse interface was estimated using physical values, where a particle diameter of 100 nm was used, similar to the experiments presented by Elias et al 9 Future investigations will include the influence of the interface thickness on the migration of particles near fluid–fluid interfaces (or, similarly:, changing the particle size), possibly with relation to a sharp-interface model. In the present model, the motion of the contact line across the surface of the particle is governed by the Cahn–Hilliard mobility in a phenomenological sense: contact line pinning and hopping, which are known to be important in the adsorption of particles at interfaces, 39 are not described explicitly. A possible extension of the model is to explicitly describe the roughness of the particle surface.…”
Section: Discussion and Conclusionmentioning
confidence: 99%